THE PROHIBITION OF DISCRIMINATION OF ART. 14 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS IN MATTERS OF INHERITANCE AND AFILLIATION REGARDING THE PROVISIONS OF THE NEW CIVIL CODE - CARLA ALEXANDRA ANGHELESCU; GABRIEL BOROI (Challenges of the Knowledge Society)
Taking into consideration the provisions of the New Civil Code that has recently entered into force, the study focuses on the analysis of its provisions regarding matters of inheritance and affiliation in order to establish their compliance with the established case-law of the European Court of Human Rights in interpreting article 14 of the European Convention on Human Rights.